Estructuración del sistema de gestión por procesos para el área de Salud No. 5 La Magdalena - Ochoa Ushiña, Sonia de las Mercedes (2006)
This research aims to reduce the rate of bureaucracy in health services by public bodies as many of the processes are obsolete and redundant and do not adapt to the demands of a constantly changing environment which affects dissatisfaction client.